Adobe Premiere Pro : 2024 release - Jago, Maxim (Classroom in a book., 2024)
Adobe Premiere Pro Classroom in a Book 2024 release contains 17 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you.